A espacialização do cosplay no eixo Goiânia e São Paulo: cultura e imaginário - Louza, Yhanka Jesus (2022)
The present research investigates and contextualizes the cosplay culture in the metropolis of Goias and São Paulo, from the central subjects that are the cosplayers. These can be described as fans of pop culture, of characters from various narratives such as movies, TV series, books, comics, anime, and manga and who gather together dressed as media characters, establishing a bond. This bond interferes in the imaginary and in the way these people behave on a daily basis. We also seek to understand in what way this practice is spatialized in the capitals chosen as a spatial cutout, throughout the meetings that take place, and the possibilities and facilities that metropolises can bring so that this cultural group inhabits its spaces and remains. It also shows the possibility of cosplay being able to transform the landscape of several places, whenever cosplayers gather in events located in the urban space of Goiânia and São Paulo. Finally, there is the intention of showing in an approximate way the experiences caused by such culture, presenting stories shared during interviews, analyzing what it means for the subjects to be part of this context.